Oil and Gas 1: Student's Book - Lansford L. Lewis (Oxford English for Careers)
gives you the language, information, and skills you need to start your career. Learn the English you need to do the job, practise-fcnguage in real work situations, and learn specialist vocabulary on every page: Ifs my job - real people talk about their work in a variety of oil and gas careers Number talk - activities using nmbers and measurements in communication for work Writing bank - extra practice in writing reports, notes, and emails British and American English terms defined throughoutOnline interactive exercises to revise and recycle language: ww.oup.com/ <http://www.oup.com/>elt/oefc The Teacher's Resource Book provides everything you need to teach English for oil and gas with confidence: Background information and specialist knowledge of the subject.